Pengaruh Angka Partisipasi Sekolah (APS) Dan Kemiskinan Terhadap Indeks Pembangunan Manusia (IPM) Pada Kabupaten Di Provinsi Sumatera Barat - Olina Aprilia; Efni Cerya (Universitas Negeri Padang, 2023)
This study’s purpose is to determine the effect of School Enrollment Rate (APS) and Poverty to Human Development Index (HDI) in districts on West Sumatera. This study is classified as descriptive-associative research and uses e-views 9 programs for processing data, the data using secondary data from the data of 12 districts on West Sumatera. This study uses linear regression analysis of panel data with approached the Random Effects Models. The results of this study indicate that APS has a significant positive effect on HDI. Poverty has a significant negative effect on HDI. And both APS and Poverty affect HDI.